Unpacking the Role of Interdisciplinary Collaboration in Surgical Teams: A Critical Analysis of Operational Efficiency and Patient Outcomes - Alanazi, Amer Owaid; Alanazi, Mohammed Abdulhadi; Alobaid, Abdullah Obaid; AL Sugyani, Abdulrhman Marjan Farg; Alrkabi, Sultan Abdullah; Alanazi, Fahad Mohammed; Alanazi, Nafea Aziz; Alanazi, Bander Hani; Alanezi , Nail Saqeer; Alenezi, Mohammed Awied (Journal of Ecohumanism, 2024)
Interdisciplinary collaboration is essential for effective surgical operations, impacting both operational efficiency and patient outcomes. This critical analysis explores the dynamics of teamwork within surgical teams, focusing on how structured collaboration can streamline procedures, enhance resource management, and reduce surgical errors. Drawing from existing literature and recent empirical data, the article examines key factors that contribute to successful interdisciplinary collaboration, including role clarity, communication protocols, and mutual respect among team members. Findings reveal that well-coordinated interdisciplinary efforts lead to improved patient safety, reduced postoperative complications, and increased patient satisfaction. However, barriers such as hierarchical structures and communication breakdowns remain significant challenges. This analysis highlights actionable recommendations for fostering effective collaboration in surgical settings, such as targeted training, standardized communication strategies, and clear role definitions. Ultimately, strengthening teamwork within surgical teams not only optimizes operational efficiency but also enhances patient care quality, underscoring the importance of collaborative practices in modern healthcare.